Characteristics influencing the price of fed cattle sold on the Fed Cattle Exchange online platform - Herbst, Emilie (Kansas State University, 2018)
With the decline in negotiated trade in the live cattle cash market, feedyards and packers are looking for new ways to increase cash trade. An online, fed cattle auction was created to increase transparency as well as increase the cash trade. Hedonic models have been used heavily to study feeder cattle and the value placed on their characteristics. There is little hedonic modeling done on live cattle and the value of their characteristics. The Fed Cattle Exchange is a new online platform, therefore, no research has been done on it. The objective of this research is to use hedonic modeling to determine the value packers place on characteristics of each lot of fed cattle sold. These characteristics include, weight, number of head, sex, days on feed, location, yield grade, quality grade, delivery time period, and use of a beta-agonist. This research found that use of a beta agonist, location, days on feed, number of head, weight, delivery time frame as well as inclusion of a Select percentage were all statistically important to the price paid. Results will benefit feedyards by informing the sellers on what buyers find the most desirable. This will help with both feedyard procurement practices as well as feedyard management practices.
Keywords: Fed cattle; Hedonic model; Online auction; Negotiated Trade; Fed cattle exchange